Proses Berpikir Penyelesaian Proyek Bertingkat Medode Flipped Classroom di Masa Pandemi COVID-19 - indah rahayu; eric dwi putra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
The COVID-19 pandemic has had a major impact on the world of education, especially in universities. The implementation of face-to-face lectures has turned virtual by utilizing internet technology. Blended learning began to be implemented by lecturers to unify the face-to-face and online learning processes. One of the methods used is Flipped classroom; this method has many benefits, such as students will have new knowledge, more independent, more active and more creative and critical in confronting cases. The research was carried out using qualitative approach with descriptive type. The research subjects were 4 semester 3 students with 2 high abilities (ST1, ST2) and 2 low abilities (SR1, SR2). The results of expert validation for testing the quality of test instruments and interviews show that all of them are valid and can be used. Then for the results of the research, it is said that the thinking process of students is at the expert level, high ability students can complete well and the given project tasks, low ability students are at the novice level and have not been able to complete the project. Keywords: thinking process, multilevel project, flipped classroom, pandemic covid-19